PENGARUH PELATIHAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA UNTUK MENINGKATKAN SEMANGAT KERJA DAN KINERJA TENAGA PENDIDIK - Khotim Fadhli (Fakultas Ekonomi Universitas KH. A. Wahab Hasbullah Tambakberas Jombang, 2020)
This study aims to analyze the effect of training, human resource development, spirit at work, and teacher performance in non-formal education through a positivist approach. The population is Yalatif Indonesia Foundation educators with a sample of 50 non-formal education tutors. The analysis technique used is Path Analysis. The results showed that the existence of training and human resource development had an effect on spirit at work of the teaching. This means that by carrying out training and human resource development will foster the confidence of educators that this institution is not only pursuing profit, and the institution where they work has attention to educators. The training that was held was proven to get a positive response. This proves that the teaching staff who take part in the training get the attention of the institution, where the teaching staff feels that the teaching staff is an asset for the institution. In addition, educators also feel that their presence is not only as a worker, but also for their interests. The results of the analysis show that the morale of the teaching force has an effect on the performance of the teaching force. This shows that with better morale, educators are able to carry out their duties and jobs better. Keywords: Training, Human Resource Development, Spirit at Work, Teacher Performance